Association between prenatal psychological stress and oxidative stress during pregnancy. Issue 4 (30th March 2018) - Eick, Stephanie M.; Barrett, Emily S.; van 't Erve, Thomas J.; Nguyen, Ruby H. N.; Bush, Nicole R.; Milne, Ginger; Swan, Shanna H.; Ferguson, Kelly K.
Abstract: Background: Prenatal psychological stress during pregnancy has been associated with adverse reproductive outcomes. A growing animal literature supports an association between psychological stress and oxidative stress. We assessed this relationship in pregnant women, hypothesising that psychological stress is associated with higher concentrations of oxidative stress biomarkers during pregnancy. Methods: Psychosocial status and stressful life events (SLE) were self‐reported. 8‐iso‐prostaglandin F2α (8‐iso‐PGF2α ) was measured as a biomarker of oxidative stress in urine samples at median 32 weeks' gestation. We examined SLEs individually (ever vs never) and in summary (any vs none) and psychosocial status as measured by individual subscales and in summary (poor vs good). Linear models estimated associations between these parameters and urinary 8‐iso‐PGF2α concentrations after adjusting for covariates. Results: The geometric mean of 8‐iso‐PGF2α was significantly higher among pregnant women who were non‐White, smokers, had less than a college education, higher pre‐pregnancy BMI and were unmarried. Having ever had a death in the family (n = 39) during pregnancy was associated with a 22.9% increase in 8‐iso‐PGF2α in unadjusted models (95% confidence interval [CI] 1.50, 48.8). Poor psychosocial status was associated with a 13.1% (95% CI 2.43, 25.0) greater mean 8‐iso‐PGF2α in unadjusted analyses. Associations were attenuated, but remained suggestive, after covariate adjustment. Conclusions: These data suggest that 8‐iso‐PGF2α is elevated in pregnant women with who are at a sociodemographic disadvantage and who have higher psychological stress in pregnancy. Previous studies have observed that 8‐iso‐PGF2α levels are associated with adverse birth outcomes, oxidative stress could be a mediator in these relationships.